2015
DOI: 10.1016/j.schres.2015.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive remediation for adolescents with 22q11 deletion syndrome (22q11DS): A preliminary study examining effectiveness, feasibility, and fidelity of a hybrid strategy, remote and computer-based intervention

Abstract: Background 22q11DS is a multiple anomaly syndrome involving intellectual and behavioral deficits, and increased risk for schizophrenia. As cognitive remediation (CR) has recently been found to improve cognition in younger patients with schizophrenia, we investigated the efficacy, feasibility, and fidelity of a remote, hybrid strategy, computerized CR program in youth with 22q11DS. Methods A longitudinal design was implemented in which 21 participants served as their own controls. Following an eight month bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 48 publications
3
48
0
Order By: Relevance
“…The present paper extends our previous work by investigating the durability of the effects of a remote, computerized hybrid CR programme for youth with 22q11DS. Specifically, our goal was to determine if the salutary effects of CR on several key domains of cognition in youth with 22q11DS reported in our previous paper would persist at 6 months after the cessation of CR treatment.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…The present paper extends our previous work by investigating the durability of the effects of a remote, computerized hybrid CR programme for youth with 22q11DS. Specifically, our goal was to determine if the salutary effects of CR on several key domains of cognition in youth with 22q11DS reported in our previous paper would persist at 6 months after the cessation of CR treatment.…”
Section: Introductionsupporting
confidence: 57%
“…Cognitive improvement following CR has been reported in the areas of processing speed, working memory, verbal memory, problem solving, executive functioning, cognitive flexibility and social functioning for young adults and adolescent populations at risk for, or with, early onset schizophrenia . Recent studies found computerized, CR interventions to be feasible and effective with similar populations as well as youth with 22q11DS …”
Section: Introductionmentioning
confidence: 99%
“…This has important implications for clinical practice, as it suggests that EF could be a valuable target for treatment in children with 22q11DS. This study provides support for assessing the efficacy of preventative cognitive remediation (CR) interventions for children with 22q11DS, such as the computer-based CR intervention investigated by Mariano and colleagues (Mariano, Tang, Kurtz, & Kates, 2015, 2016). That is, Mariano and colleagues administered a longitudinal, computer-based cognitive remediation program (Bracy et al, 1999) to 21 adolescents with 22q11DS, and observed that participants exhibited significant improvements in working memory, shifting attention, and cognitive flexibility.…”
Section: Discussionmentioning
confidence: 74%
“…Harrell et al 86 found that a short-term CR intervention program was feasible in a small sample of children with 22q11.2DS, who showed improvement in a cognitive composite score and simple processing speed. Mariano and colleagues 87 found significant post-treatment improvements with small to medium effect-sizes in working memory, shifting attention, and cognitive flexibility utilizing a longer-term (average treatment time of approximately 8 months), remotely-administered, computer-based cognitive training program. The study provided support for the feasibility of a relatively intense training schedule with individuals with 22q11.2DS, and incorporated an analysis of fidelity of the coach’s interventions in the strategy-based/drill-and-practice approach.…”
Section: Discussionmentioning
confidence: 99%